Differences and similarities between users of traditional healing and other CAM modalities in the seventh survey of the Tromsø Study - Kristoffersen, Agnete Egilsdatter; Broderstad, Ann Ragnhild; Musial, Frauke; Stub, Trine (2019)
Poster presented at the ICCMR International conference in complementary medicine research, Brisbane, 07.05. - 10.05.19, http://iccmr2019.com/ , arranged by ISCMR International society complementary medicine research.